Maqasid al-Shariah in Contemporary Legal Systems: An Analysis of Digital Rights and Privacy Protection - Arminsyah Arminsyah (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
Maqasid al-Shariah, as the foundational framework of Sharia’s objectives, offers universal principles that remain highly relevant in addressing contemporary legal challenges. This article examines the application of Maqasid al-Shariah within modern legal systems, with a particular focus on the protection of digital rights and privacy—an increasingly urgent issue in the era of digital transformation. Specifically, this study explores how the objectives of preserving intellect (hifz al-aql) and property (hifz al-mal) intersect with current data protection and privacy regulations in digital environments. Employing a qualitative methodology grounded in literature review and legal analysis, the article finds that Maqasid al-Shariah offers a robust ethical framework capable of safeguarding both individual and collective interests in a balanced manner while upholding spiritual and moral values. The study also addresses the challenges of integrating Maqasid al-Shariah with secular legal systems, especially amid globalization and rapid technological advancement. The findings suggest that embedding Maqasid al-Shariah into digital privacy regulations could serve as a strategic approach to building legal systems that are more inclusive, adaptive, and just. Therefore, the article concludes by emphasizing the need to further elaborate the policy implications of this framework to enhance its practical relevance and academic contribution. Ultimately, Maqasid al-Shariah is demonstrated to be both relevant and applicable as an ethical foundation for confronting legal challenges in the digital age.